2012
DOI: 10.1068/c11167b
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Minority Business Support in the West Midlands: Challenges and Developments

Abstract: We examine the challenges and developments relating to the support of ethnic minority businesses (EMBs). The challenges pertain to the distinctiveness of business support needs, the 'mainstreaming' of EMB support, and the dynamics of delivery. An 'engaged scholarship' approach is adopted, on the basis of an examination of business support providers in the West Midlands. We fi nd considerable evidence of 'policy learning' in respect of these challenges. Hence, a nuanced approach to EMB support needs is in evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 34 publications
0
45
0
1
Order By: Relevance
“…Consequently, policy interventions reflect tailored and bespoke support for: women-owned businesses (Marlow et al, 2008;Rouse and Kitching, 2006;Wilson et al, 2004); disabled people (Kitching, 2006); ethnic minorities and refugees (Deakins et al, 2003;Lyon et al, 2007;Ram and Smallbone, 2002;Ram et al, 2012); students and graduates (Pickernell et al, 2011); and rural enterprises (Anderson et al, 2005;Lee and Cowling, 2015;Smallbone et al, 2003;Sutherland and Burton, 2011).…”
Section: Entrepreneurship and Policymentioning
confidence: 99%
“…Consequently, policy interventions reflect tailored and bespoke support for: women-owned businesses (Marlow et al, 2008;Rouse and Kitching, 2006;Wilson et al, 2004); disabled people (Kitching, 2006); ethnic minorities and refugees (Deakins et al, 2003;Lyon et al, 2007;Ram and Smallbone, 2002;Ram et al, 2012); students and graduates (Pickernell et al, 2011); and rural enterprises (Anderson et al, 2005;Lee and Cowling, 2015;Smallbone et al, 2003;Sutherland and Burton, 2011).…”
Section: Entrepreneurship and Policymentioning
confidence: 99%
“…It was outlined by several researchers (e.g. Oc and Tiesdell, 1999;Ram et al, 2002;Rath, 2011;Ram et al, 2012) that there is a lack of business start-up support for the ethnic minority entrepreneurs but the current situation has been changed in the context of Aberdeen. No respondent claimed that there is a lack of business start-up support; instead they praised the local authority body and business support groups.…”
Section: Macrosphere Factors Causing Shortage Of Suitable Employeesmentioning
confidence: 99%
“…To overcome such problems, the government has promoted business support services in their various guises over the years (Mole et al, 2011;Ram et al, 2012). However, mainstream support services are not always found to be appropriate for the needs of ethnic minority businesses (Ram et al, 2006), and/or are not trusted .…”
Section: Challenges Faced By Ethnic Entrepreneurs -Regulations and Mamentioning
confidence: 99%
“…They add that not being born in Sweden and not going to the same school as others makes them outsiders, which reduces their chances against others in the competition for tender acceptance. Previous research has found that government organizations and local authorities play a significant role in encouraging networking and cooperation between small and large firms, even those competing in the same tender [109]. This was indicated as an influential factor in strengthening the relationship between the public sector and immigrant entrepreneurs [13].…”
Section: Competitionmentioning
confidence: 99%
“…The public sector could use alternative, more accessible, methods to communicate procurement opportunities with immigrant entrepreneurs. One of the most frequently used methods identified in the literature is communicating and providing business support for immigrant entrepreneurs through informal trusted networks [109], as such networks are found to be key in reinforcing the relationship between the government with ethnic minority communities [13]. These networks can even be persuaded to form trade associations to facilitate communication, information sharing and even possible joint ventures in future.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%